DAMPAK MATA KULIAH PENDIDIKAN KONSUMEN TERHADAP PERUBAHAN PERILAKU BELANJA MAHASISWA - Febriwimayani Nasution; Vina Gabriella Saragih (CV. ADIBA AISHA AMIRA, 2025)
The evolving digital consumption landscape and increasing consumptive patterns among university students necessitate comprehensive consumer literacy. This study aims to analyze the impact of Consumer Education courses on changes in student shopping behavior. Employing a quantitative method with quasi-experimental design, the research involved 120 students divided into experimental (course participants) and control groups. Data were collected through structured questionnaires measuring four dimensions of shopping behavior: purchase rationality, consumer rights awareness, product evaluation capability, and financial management. Results indicate significant differences (p<0.05) between experimental and control groups across all shopping behavior dimensions following the learning intervention. Students who participated in the Consumer Education course demonstrated an average increase of 32% in purchase rationality, 45% in consumer rights awareness, 38% in product evaluation capability, and 41% in financial management. These findings confirm that formal consumer education plays a crucial role in fostering wiser and more responsible shopping behavior in the digital era.